Discussion on The Curriculum Modification Model for Preschool Inclusion - Shu-hsien Tseng (National Taipei University of Education, 2021)
With the trend of inclusion, young children with special needs who attend regular classrooms are increasing in number. Also, as the gap in the context of inclusion among the developmental levels and special needs of preschool children becomes larger after the integration of kindergartens and nursery schools, preschool teachers need to implement differentiated instruction according to students' individual needs, and make flexibly adjustment to the instructional content and assessments to enhance learning achievement and to guide students' development. An essential way to implement differentiated instruction is through curriculum modification. However, the current literature and practice of preschool curriculum modification primarily focus on external modification strategies. Nevertheless, an increasing amount of preschool studies have confirmed the important role played by children's key abilities and self-regulation in their development and learning. Studies show that internal modification strategies that emphasize on adjusting children's behaviors to establish their inner abilities is a more indispensable part of curriculum modification. Therefore, this article reviews the literature critically and proposes a ‟PEACI curriculum modification model" that covers internal and external modification strategies as a frame reference for researchers and practitioners to design adaptive curriculum and instruction for preschool inclusion. It is also suggested that related policies and trainings should emphasize on internal modification expanding from current eight strategies of three dimensions to 10 strategies of five dimensions of PEACI model, to enhance teachers' efficacy in implementing differentiated instruction.